2020
DOI: 10.2478/izajole-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of co-worker wage gains

Abstract: We address the presence, magnitude, and composition of wage gains related to former co-workers and discuss the mechanisms that could explain their existence. Using Hungarian linked employer–employee administrative data and proxying actual co-workership with overlapping work histories, we show that the overall wage gain attributable to former co-workers consists of multiple elements: a contact-specific, an individual-specific, a firm-specific and a match-specific component. Former co-workers, besides the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This model shows that the consequence of having former co-workers at a company is increased starting wages. The existence of such a wage gain has been shown empirically-a fact that has been explained by two rationales: First, that by network information firms can select workers with better unobserved skills, and secondly, that such networks enable workers to choose from higher productivity (and thus higher paying) firms [27,28]. Another consequence is that employers are more likely to hire workers with whom their current workers have connections [29].…”
Section: Introductionmentioning
confidence: 99%
“…This model shows that the consequence of having former co-workers at a company is increased starting wages. The existence of such a wage gain has been shown empirically-a fact that has been explained by two rationales: First, that by network information firms can select workers with better unobserved skills, and secondly, that such networks enable workers to choose from higher productivity (and thus higher paying) firms [27,28]. Another consequence is that employers are more likely to hire workers with whom their current workers have connections [29].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies, with respect to data and approach, have already demonstrated that workers are more likely to get their new jobs at firms where their acquaintances are employed (Saygin, Weber and Weynandt, 2021), and also that co-workers affect wages to a meaningful extent (Boza and Ilyés, 2020;Glitz and Vejlin, 2021). Some of the results even shed light on gender differences: women benefit less from their former co-workers in terms of wages (Boza and Ilyés, 2020) and they receive a lower amount of work-related information from their employed former co-workers (Saygin, Weber and Weynandt, 2021). However, none of the previous studies focused exclusively on or addressed comprehensively the differences in the measured effects by gender.…”
Section: Introductionmentioning
confidence: 66%
“…Informal ties, through information delivery, referral and signaling, can enhance the individuals' job finding chances (Holzer, 1988;Cingano and Rosolia, 2012;Saygin, Weber and Weynandt, 2021). Moreover, they can contribute to the creation of better employer-employee matches (Dustmann et al, 2016;Boza and Ilyés, 2020) which typically couples with longer tenure, lower turnover and higher wages (Hensvik and Skans, 2016;Glitz and Vejlin, 2021). The benefits acquired through informal search, however, are highly dependent on the characteristics of the individuals and their network quality.…”
Section: Gender Segregation In Labor Market Networkmentioning
confidence: 99%
See 2 more Smart Citations